2020
DOI: 10.1007/s40477-020-00456-9
|View full text |Cite
|
Sign up to set email alerts
|

Alanine aminotransferase and spleno-portal dynamics affect spleen stiffness measured by point shear-wave elastography in patients with chronic hepatitis C in the absence of significant liver fibrosis

Abstract: Background Spleen stiffness (SS) has gained a lot of interest in the context of liver cirrhosis and portal hypertension stratification. However, there is a paucity of data on confounding factors that may alter SS values. Methods Between January 2018 and October 2019, we enrolled 120 healthy subjects and 117 patients with hepatitis C virus (HCV) infection who did not have significant liver fibrosis (i.e., F0-1). Abdominal ultrasound evaluation was performed on each individual to measure portal vein diameter, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…LSM was performed with pSWE technology and ElastPQ evaluation protocol, using two different Philips (Philips Healthcare, Best, Netherlands) ultrasound systems: IU22 (machine 1) and Affiniti 70 (machine 2), with a 1–5 MHz convex probe. The exact acquisition of LSM, patients’ preparation and reliability criteria were already explained elsewhere [ 18 , 19 , 20 ]. Of notice, the region of interest (ROI) was always positioned at two centimeters from the liver capsule.…”
Section: Methodsmentioning
confidence: 99%
“…LSM was performed with pSWE technology and ElastPQ evaluation protocol, using two different Philips (Philips Healthcare, Best, Netherlands) ultrasound systems: IU22 (machine 1) and Affiniti 70 (machine 2), with a 1–5 MHz convex probe. The exact acquisition of LSM, patients’ preparation and reliability criteria were already explained elsewhere [ 18 , 19 , 20 ]. Of notice, the region of interest (ROI) was always positioned at two centimeters from the liver capsule.…”
Section: Methodsmentioning
confidence: 99%
“…Considering spleen vein was oppressed by pancreatic pseudocysts, disorder of blood flow in the splenic vein may lead to spleen congestion, which increased its stiffness[ 17 ]. Other authors had said that spleen stiffness may serve as a surrogate for the dynamic component of esophageal varices, which pointed out that spleen stiffness has been considered markers of esophageal varices, life-threatening upper gastrointestinal bleeding[ 18 - 20 ]. In short, sonographers should pay another attention to the stiffness of spleen when sinistral portal hypertension was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fibrosis scoring by liver elastography in patients with HCV was influenced by serum transaminase levels [ 29 ]. Measurement of spleen stiffness by point shear-wave elastography was also affected by serum transaminase levels in patients with HCV infection [ 30 ]. These studies showed that serum transaminase levels, which are related to inflammation and virus-induced cytolysis, are confounding factors in noninvasive techniques to measure tissue stiffness [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of spleen stiffness by point shear-wave elastography was also affected by serum transaminase levels in patients with HCV infection [ 30 ]. These studies showed that serum transaminase levels, which are related to inflammation and virus-induced cytolysis, are confounding factors in noninvasive techniques to measure tissue stiffness [ 29 , 30 ]. The decline of the ARFI score three months after the end of DAA therapy is most likely a consequence of lower serum transaminase levels rather than an improvement in liver stiffness.…”
Section: Discussionmentioning
confidence: 99%